Role of Intracellular Proteases in the Antibiotic Resistance, Motility, and Biofilm Formation of Pseudomonas aeruginosa - Fernández, Lucía (American Society for Microbiology, 2012)
Pseudomonas aeruginosa possesses complex regulatory networks controlling virulence and survival under adverse conditions, including antibiotic pressure, which are interconnected and share common regulatory proteins. Here, we screen a panel of 13 mutants defective in intracellular proteases and demonstrate that, in addition to the known alterations in Lon and AsrA mutants, mutation of three protease-related proteins PfpI, ClpS, and ClpP differentially affected antibiotic resistance, swarming motility, and biofilm formation.